Local full-thickness skin graft of the donor arm—a novel technique for the reduction of donor site morbidity in radial forearm free flap. Issue 8 (August 2015) - Riecke, B.; Assaf, A.T.; Heiland, M.; Al-Dam, A.; Gröbe, A.; Blessmann, M.; Wikner, J.
Abstract A novel technique to reduce donor site morbidity after radial forearm free flap (RFFF) harvest, using a local full-thickness skin graft (FTSG), is described. Thirty consecutive patients undergoing RFFF for head and neck reconstruction were enrolled in a prospective study. Donor site defect closure was performed with spindle-shaped FTSGs excised from the wavelike skin incision made for the vascular pedicle. Both the removal site of the FTSG on the volar forearm and the covered RFFF donor site healed uneventfully in 29 cases, with no impairment of function related to the skin graft. No skin graft failure and no exposure, tenting, or adherence of the flexor tendons occurred. All patients expressed satisfaction with postoperative pain, the functional outcome, and cosmetic appearance. Primary donor site defect closure could be achieved in all cases with the use of a local FTSG. This graft can be gained at the access incision for the vascular pedicle, avoids expansion of the incision for a local flap technique, and does not prolong wound healing, and thus reduces both donor site and graft site morbidity of the RFFF. This technique leads to an inconspicuous aesthetic result with no apparent relevant functional deficits and avoids the need for a second donor site.